1998
DOI: 10.1007/s004649900820
|View full text |Cite
|
Sign up to set email alerts
|

A cost and outcome comparison between laparoscopic and Lichtenstein hernia operations in a day-case unit

Abstract: Although the Lichtenstein operation is cheaper for the hospital, the total costs for working patients are lower with the laparoscopic technique, when the cost of lost work days is factored into overall expense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 15 publications
1
85
0
5
Order By: Relevance
“…Thirty-three randomized controlled trials with a total of 5,053 random patients were used for the evaluation [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45]. Due to the separate publication of partial aspects [40, 45]and late results [11, 12, 14, 18], a total of 36 publications was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three randomized controlled trials with a total of 5,053 random patients were used for the evaluation [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45]. Due to the separate publication of partial aspects [40, 45]and late results [11, 12, 14, 18], a total of 36 publications was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 20 million groin hernioplasties are performed each year worldwide, over 17,000 operations in Sweden, over 12,000 in Finland, over 80,000 in England and over 8,00,000 in the USA [25][26][27][28][29]. Countless studies have been reported in the medical literature in attempts to improve the overall out-comes following hernia operations and, due to this fact, the procedure has The postoperative complications with LR + Herniorrhaphy [Table / Fig 14] in the study subjects approximate to 0.02% (n=13), that is very less.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] In spite of all these benefits, the use of laparoscopy in inguinal hernia surgery has not been established among surgeons on a wide scale.…”
Section: Mechanism Of Actionmentioning
confidence: 99%